Deciphering the genome of constitutionalism : the foundations and future of constitutional identity - Hirschl, Ran; Roznai, Yaniv (Cambridge , United Kingdom ; New York, NY : Cambridge University Press, 2024)
"Featuring key scholars of comparative constitutionalism, constitutional theory, and constitutional politics, this book provides a comprehensive, theoretical, comparative, normative, and empirical account of the concept of constitutional identity. It will appeal to scholars, students, jurists, and constitutional drafters alike"--
Rousseau's sovereignty and the concept of constitutional identity, by Howard Schweber -- Constitutional identity-cracking the genetic code of the constitution, by Monika Polzin -- Constitutional identity as discourse : misp-identity and dis-identity, by Jaclyn L. Neo -- Constitutional identity and constitutional revolution, by Stephen Gardbaum -- The death of the constituent power, by Victor Ferreres Comella -- Constitutional identity as a source of ontological security, by Joanne Wallis -- The crisis in, and of, constitutional identity, by Upendra Baxi -- Confucian constitutional identity, by Bui Ngoc Son -- "(A-)religious & democratic" militant dual constitutional identities and the turn to illiberalism : the case of France, by Eugénie Mérieau -- Constitutional identity in Bangladesh : complexity and contestations, by Ridwanul Hoque -- Clashing identities? traditional authority and constitutionalism in Africa, by Heinz Klug -- Imposed revolution? "August Revolution," "Imposed constitution," and the identity of the constitution of Japan, by Keigo Komamura -- India : a constitution in search of an identity, by Gautam Bhatia -- "This is (not) who we are" : reflections on 1619 and the search for a singular constitutional identity, by Sanford Levinson -- Constitutional aspirationalism revisited, by Justin Dyer -- The constitution at war with itself : race, citizenship, and the forging American constitutional identity, by George Thomas -- Constitutional identity, constitutional politics, and constitutional revolutions, by Mark A. Graber -- American constitutional exceptionalism, constitutional identity, and democracy, by Miguel Schor -- Constitution making and disharmonic identity, by Asli Bâli and Hanna Lerner -- Constitutional identity and unamendability, by Oran Doyle -- Illiberal constitutionalism and the abuse of constitutional identity, by Gabor Halmai and Julian Scholtes -- Deconstructing constitutional identity in light of the turn to populism, by Michel Rosenfeld -- Unconstitutional constitutional identities in the European Union, by Pietro Faraguna -- What counts as constitutional identity? by Mila Versteeg -- Contrariness and contradiction in constitutional law, by Zachary Elkins and Tom Ginsburg -- Conclusion : the past, present, and future of constitutional identity, by Christina Bambrick and Connor M. Ewing.
First published.
Includes bibliographical references and index.
SOL
Hye Trade International
Keywords: Constitutional law; Constitutions; Law